Direct cost does not impact on young children’s spontaneous helping behavior - Nielsen, Mark; Gigante, Julia; Collier-Baker, Emma (Frontiers in Psychology, 2014)
The propensity of humans to engage in prosocial behavior is unlike that of any other species. Individuals will help others even when it comes at a cost to themselves, and even when the others are complete strangers. However, to date, scant empirical evidence has been forthcoming on young children’s altruistic tendencies. To investigate this 45 4-year-olds were presented with a task in which they had opportunity to help an adult confederate retrieve a reward from a novel box. In a control condition children were given no information about the effect of potential helping behavior. Alternatively they were informed that helping would either cost them (ie., they would miss out on getting the reward) or benefit them (ie., they would get the reward). It was hypothesized that children would be less likely, and slower, to help in the Cost condition, compared to the other two conditions. This hypothesis was not supported: Children across all conditions provided help at near ceiling levels.